Study of oro-facial deformities in treated leprosy patients in central India - Deshpande, Amit V.; Chaudhary, Sanjeev M.; Mukhi, J. I.; Bansode, V. W.; Morey, P. D. (International Journal Of Community Medicine And Public Health, 2017)
Background: Though leprosy has ceased to be a chronic disease, the impairments present at diagnosis or those which develop after diagnosis may have a lasting effect on the functioning of those who have been patients. This study is an attempt to clinically evaluate the orofacial lesions and deformities of treated leprosy patients, and see whether they have received any rehabilitation services. Methods: This was a hospital based cross sectional study conducted in a tertiary health care centre at Nagpur. All treated leprosy patients coming to the Out patients department of Skin and Venereal Diseases centre of the institute were examined and details regarding rehabilitation services received by them were inquired. Results: A total of 30 patients were studied of whom male and female were 15 each. Oro-facial lesions were seen in 20 patients of whom 11 were males and 9 were females. The most common lesion was in tongue (depappilated/fissured/deviated) in males and madarosis in females. Shrunken or erythematous uvula was the least common finding. Deformities of hands and feet were more common in females while deformity of eyes was more common in males. Utilization of rehabilitative services was very poor. Conclusions: It can be concluded from the results that leprosy as a disease is being treated successfully but the Oro-facial lesions and deformities are significant and utilization of rehabilitation is poor.